2020
DOI: 10.1002/lno.11626
|View full text |Cite
|
Sign up to set email alerts
|

Aufeis fields as novel groundwater‐dependent ecosystems in the arctic cryosphere

Abstract: River aufeis (ow 0 fīse) are widespread features of the arctic cryosphere. They form when river channels become locally restricted by ice, resulting in cycles of water overflow and freezing and the accumulation of ice, with some aufeis attaining areas of $ 25 + km 2 and thicknesses of 6+ m. During winter, unfrozen sediments beneath the insulating ice layer provide perennial groundwater-habitat that is otherwise restricted in regions of continuous permafrost. Our goal was to assess whether aufeis facilitate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…72 In addition, potential attention so far. 28 The results of the accuracy assessment support that a machine learning approach is suitable to map icing/aufeis and that the method can be transferred to other regions. Unlike thresholds, deviations in spectral properties do not require manual adjustments and have little influence on the predictions of the model, if the training samples are representative of the target classes.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…72 In addition, potential attention so far. 28 The results of the accuracy assessment support that a machine learning approach is suitable to map icing/aufeis and that the method can be transferred to other regions. Unlike thresholds, deviations in spectral properties do not require manual adjustments and have little influence on the predictions of the model, if the training samples are representative of the target classes.…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, remote sensing provides the opportunity to monitor such changes, despite data availability remaining the main obstacle for long‐term monitoring in the region. The widespread occurrence of aufeis in the Trans‐Himalaya 31 offers the opportunity not only to investigate the hydrology or physicomechanical process but also their role for river ecology, downstream habitats or local communities – aspects which have not received much attention so far 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of global warming, interactions between groundwater flow and surface water may cause the release of carbon trapped in permafrost and aggravate the greenhouse effect (Harlan, 1973;Solomon et al, 2007;Schaefer et al, 2011;Wisser et al, 2011;Mckenzie and Voss, 2013;Connolly et al, 2020;Behnke et al, 2021). Because of the heat released by the movement of groundwater in the subsurface layer and the thermal insulation effect of the surface ice layer, saturated sediments are not frozen year round and provide interstitial habitats for groundwater fauna (Schohl and Ettema, 1990;Clark and Lauriol, 1997;Alekseyev, 2015;Huryn et al, 2020;Terry et al, 2020). All these findings undoubtedly confirm the importance of groundwater flow in cold-region hydrological systems.…”
Section: Introductionmentioning
confidence: 81%
“…Springs that feed aufeis accumulations tend to be sites of particularly dense aquatic and riparian vegetation and provide overwintering sites for fish including Arctic char (Salvelinus alpinus) (Childers et al, 1977). Huryn et al (2021) found that aufeis facilitates the existence of rich and spatially extensive groundwater-dependent invertebrate communities with significantly different community structure than those present in surface habitats. River corridors in this tundra environment attract migratory songbirds (Winner, 2003), shorebirds (Johnson et al, 2007), waterfowl (Larned et al, 2012), and willow ptarmigan (Lagopus lagopus) (Christie et al, 2014), as well as moose (Alces alces) (Zhou et al, 2020) and other wildlife.…”
Section: Study Areamentioning
confidence: 99%